Dukungan Sosial Terhadap Kesehatan Jiwa Ibu Hamil di Wilayah Kerja Puskesmas Peulumat Aceh Selatan - Syarifah Masthura; Cut Nur Hafizhah; Jubir Jubir (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
The lack of social support from family and peers is one of the factors contributing to psychological distress in pregnant women. Pregnant women often feel that their pregnancy is not valued by their families and peers, leading to stress that can negatively impact fetal development and the mother's well-being. The purpose of this study was to analyze the determinants of social support in relation to the mental health of pregnant women in the working area of Peulumat Public Health Center, South Aceh. This study used a quantitative approach with a descriptive correlational survey and a cross-sectional design. The sample consisted of 68 pregnant women selected randomly. The research was conducted from May 1 to 11, 2024, in the working area of Peulumat Public Health Center, South Aceh. The study found a significant influence of family support on the mental health of pregnant women in the area, with a p-value of 0.007. Additionally, peer support also had a significant effect on the mental health of pregnant women, with a p-value of 0.002. These findings highlight the importance of social support from family and peers in maintaining the mental health of pregnant women. Therefore, it is recommended that pregnant women seek and maintain social support from their surroundings to enhance motivation, encouragement, and lead a healthier lifestyle during pregnancy.